2002
DOI: 10.1017/s0952836902000961
|View full text |Cite
|
Sign up to set email alerts
|

Landscape structure and food supply affect eagle owl (Bubo bubo) density and breeding performance: a case of intra‐population heterogeneity

Abstract: During the 20th century, Mediterranean landscapes underwent extensive changes. In particular, decreasing grazing pressure combined with abandonment of agricultural uplands favoured the development of Mediterranean forests with a corresponding reduction of open habitats and landscape diversity. In some parts of the Mediterranean basin, including our study area, the reduction of open landscapes took place at the same time as a rapid decline in rabbits as a result of myxomatosis. This study assesses the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
133
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(147 citation statements)
references
References 16 publications
8
133
1
Order By: Relevance
“…Holt 1985;Morris 1988;Ferrer & Doná zar 1996;Delibes et al . 2001; Penteriani et al 2002a). The populations of territorial and solitary breeding species are often regulated through site dependence (Rodenhouse et al 1997(Rodenhouse et al , 1999, that is, their breeding performance is strongly determined by the spatially heterogeneous distribution of resources within heterogeneous landscapes.…”
mentioning
confidence: 99%
“…Holt 1985;Morris 1988;Ferrer & Doná zar 1996;Delibes et al . 2001; Penteriani et al 2002a). The populations of territorial and solitary breeding species are often regulated through site dependence (Rodenhouse et al 1997(Rodenhouse et al , 1999, that is, their breeding performance is strongly determined by the spatially heterogeneous distribution of resources within heterogeneous landscapes.…”
mentioning
confidence: 99%
“…Although an increased risk of predation at hedgerows may explain the foraging activity of the hedgehogs in the current study, there are only a small number of potential avian predators in Ireland. The eagle owl [ Bubo bubo (Linnaeus) ] is a signifi cant predator of hedgehogs in areas of Europe where the two species coexist (Marchesi et al 2002, Penteriani et al 2002. In France, hedgehogs were amongst the most common mammalian prey consumed by eagle owls (Penteriani et al 2002 ) and hedgehogs also dominated their prey in Italy (Marchesi et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…The eagle owl [ Bubo bubo (Linnaeus) ] is a signifi cant predator of hedgehogs in areas of Europe where the two species coexist (Marchesi et al 2002, Penteriani et al 2002. In France, hedgehogs were amongst the most common mammalian prey consumed by eagle owls (Penteriani et al 2002 ) and hedgehogs also dominated their prey in Italy (Marchesi et al 2002 ). (Riber 2006 ), as well as areas where they are not, e.g., UK (Reeve 1981, Doncaster et al 2001, Shanahan et al 2007, Hof 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Before the present study, a census of the breeding pairs of the whole massif was made (PENTERIANI et al 2001(PENTERIANI et al , 2002, and also previously observed the calling behaviour and lifecycle of the species (1997)(1998)(1999). Because divorces are not recorded in this monogamous, long-lived species, and fidelity to one breeding area was shown over several years (see review in PENTERIANI 1996), I chose 17 nest sites distributed over the whole study area, where I observed the dusk activity of the males.…”
Section: Study Area and Data Collectionmentioning
confidence: 98%
“…I carried out 17 listening sessions per month, 1 night per territory, for 5 consecutive months from early October, the time of renewal of call activity, to mid-February, when the owls start egg-laying (PENTERIANI et al 2001(PENTERIANI et al , 2002. My passive auditory sessions (PENTERIANI et al 2000) started 1 hr before sunset and ended 2 hr after sunset, by which time males left their song-posts for their hunting territories and temporarily ceased their vocal displays.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%